Incidence and estimated risk of residual transmission of hepatitis a virus and parvovirus B19 by blood transfusion in the state of Rio De Janeiro – Brazil: a retrospective study - Arthur Daniel Rocha Alves; Mariana Magaldi; Ana Carolina Sathler de Menezes; Josiane Iole França Lopes; Carlos Alexandre da Costa Silva; Jaqueline Mendes de Oliveira; Camila Mattos; Leonardo Bastos; Luiz de Melo Amorim Filho; Marcelo Alves Pinto; Luciane Almeida Amado (Virology Journal)
Abstract Background Nonenveloped viruses, such as hepatitis A virus (HAV) and parvovirus B19 (B19V), are not inactivated by detergents and solvents commonly used to manufacture plasma derivatives. Cases of transfusion-transmitted HAV and B19V have already been described in several countries. This study aimed to determine the incidence of HAV and B19V asymptomatic infections in blood donors from Rio de Janeiro and evaluate the residual risk of transmission to blood derivative recipients. Methods From 2018 to 2019, 1,204 plasma samples were tested by PCR and real-time PCR. HAV and B19V genotypes were determined through sequencing and phylogenetic analysis. The risk of transfusion transmission was determined using a Bayesian statistical approach. Results HAV-RNA and B19V-DNA were detected in 1.66 (95% CI 0.26–5.48) and 3.32 (95% CI 1.00-7.81) per 1000 donors, respectively. For HAV, all positive samples were classified as subgenotype IB. For B19V, the sequenced samples belonged to genotype 1A. The estimated numbers of infectious blood bags with HAV and B19V were 587 (95% CI 92-1936) and 880 (95% CI 355–2759), respectively. Conclusion This study originally assessed the incidence of both Hepatitis A Virus (HAV) and B19 Virus (B19V) among Brazilian blood donors, as well as the potential risk of residual transmission of these infections through blood transfusions. Our findings can contribute to future cost-effective studies aimed at implementing screening methods for these viruses, which could enhance discussion on surveillance in blood banks and protective measures for blood recipients.